1990
DOI: 10.2134/agronj1990.00021962008200040026x
|View full text |Cite
|
Sign up to set email alerts
|

Legume Species and Proportion Effects on Symbiotic Dinitrogen Fixation in Legume‐Grass Mixtures

Abstract: Optimal utilization of the N2‐fixation capability of legumes improves forage productivity and quality and reduces the need for N fertilizer. This research assessed N2 fixation in binary mixtures of white clover (Trifolium repens L.) (WC), red clover (Trifolium pratense L.) (RC), or bitdsfoot trefoil (Lotus corniculatus L.) (BT) with tall fescue (Festuca arundinacea Schreb.) (TF) at four legume proportions. Two identical experiments were established in Uruguay, one in 1983 (Exp. 1) and one in 1984 (Exp. 2) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
22
2
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 15 publications
6
22
2
1
Order By: Relevance
“…These f,rndings are similar to those reported by Boller and Nrisberger (1987) and Brophy et al (1987 Brophy et al (1987) and Mallarino et al (1990) …”
supporting
confidence: 91%
See 2 more Smart Citations
“…These f,rndings are similar to those reported by Boller and Nrisberger (1987) and Brophy et al (1987 Brophy et al (1987) and Mallarino et al (1990) …”
supporting
confidence: 91%
“…This agrees with findings by Mallarino et al (1990). They reported that legume-dominant swards were required to maximize fixed-N yields for red clover mix- (1991) that showed a decline in N transfer with time, with the decline being related to a reduced legume proportion in the sward, a loss of root-plus-crown dry matter accumulation, and reduced growth of legume and grass components of the swards.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The N-NO 3 -amounts in the soil of the grass/legume swards are only slightly reduced compared to legumes in monoculture when the catch crops are sown late or during the second research year, when growth conditions are sufficient until late autumn. Under conditions that enable growth of grass and legume, the N-NO 3 -uptake of the grass causes a temporary decrease of N-NO 3 -amounts in soil, which causes an increase of N 2 fixation (= g N/ plant) of the legume (Miller et al 1982, Mallarino et al 1990a) because nitrate affects the number and size of nodules and the fixation in active nodules (Giller 2001). This is the reason for estimated high amounts of fixed N 2 even by mixed swards.…”
Section: Discussionmentioning
confidence: 99%
“…However, the positive mixture effect is more decisive for the legume component and the estimated N transfer from the legume to the companion grass is generally on a low level. The benefit to grass plants by the neighbourhood of legumes is more distinct in perennial swards (Mallarino et al 1990a, Opitz v. Boberfeld and Biskupek 1995, Laser 1999. Apparently, the growth period is too short to enable an interspecific transfer of higher N amounts in catch crop swards, where it is more likely that surplus N from N 2 fixation is used by the following crop.…”
Section: Discussionmentioning
confidence: 99%